Necessity of Routinely Testing the Proximal and Distal Ends of Exposed Recurrent Laryngeal Nerve During Monitored Thyroidectomy - Huang, Hsiao-Yu; Lien, Ching-Feng; Wang, Chih-Chun; Wang, Chien-Chung; Hwang, Tzer-Zen; Shih, Yu-Chen; Wu, Che-Wei; Dionigi, Gianlorenzo; Huang, Tzu-Yen; Chiang, Feng-Yu (Frontiers in Endocrinology, 2022)
Objectives: Intraoperative neuromonitoring (IONM) is a useful tool to evaluate the function of recurrent laryngeal nerve (RLN) in thyroid surgery. This study aimed to determine the necessity and value of routinely testing the proximal and distal ends of RLN. Methods: In total, 796 patients undergoing monitored thyroidectomies with standardized procedures were enrolled. All 1346 RLNs with visual integrity of anatomical continuity were routinely stimulated at the most proximal (R2p signal) and distal (R2d signal) ends after complete RLN dissection. The EMG amplitudes between R2p and R2d signals were compared. If the amplitude of R2p/R2d ratio reduction (RPDR) was over 10% or loss of signal (LOS) occurred, the exposed RLN was mapped to identify the injured point. Pre- and post-operative vocal cord (VC) mobility was routinely examined with video-laryngofiberscope. Results: Nerve injuries were detected in 108 (8%) RLNs, including 94 nerves with incomplete LOS (RPDR between 13%-93%) and 14 nerves with complete LOS. The nerve injuries were caused by traction in 80 nerves, dissecting trauma in 23 nerves and lateral heat spread of energy-based devices in 5 nerves. Symmetric VC mobility was found in 72 nerves with RPDR ≤50%. The occurrence of abnormal VC mobility (weak or fixed) was 14%, 67%, 100%, and 100% among the different RPDR stratifications of 51%-60%, 61%-70%, 71%-80%, and 81-93%, respectively. Of the 14 nerves with complete LOS, all showed fixed VC mobility. Permanent VC palsy occurred in 2 nerves with thermal injury. Conclusion: Routinely testing the proximal and distal ends of exposed RLN helps detect unrecognized partial nerve injury, elucidate the injury mechanism and determine injury severity. The procedure provides accurate information for evaluating RLN function after nerve dissection and should be included in the standard IONM procedure.